2011
DOI: 10.1177/0267659111407695
|View full text |Cite
|
Sign up to set email alerts
|

Rotation thromboelastography (ROTEM) parameters are influenced by age, gender, and oral contraception

Abstract: Rotation thromboelastography (ROTEM) is a screening method that allows the rapid detection of plasma- and platelet-related haemostatic abnormalities. To use this procedure more efficiently, reference values depending on gender, age, and oral contraception are required. In this study, five cohorts of healthy subjects were examined by ROTEM upon activation of the extrinsic or intrinsic pathway of coagulation, or recalcification alone. The cohorts comprised male subjects below (1) and above (2) 45 years of age, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
3
14
1
Order By: Relevance
“…However, the age and sex dependence of ROTEM results have already been reported by Sucker et al. for the ROTEM delta device . Our reference ranges can serve as a point of orientation for other centres and help improve the discrimination between pathological and normal results.…”
Section: Discussionsupporting
confidence: 61%
“…However, the age and sex dependence of ROTEM results have already been reported by Sucker et al. for the ROTEM delta device . Our reference ranges can serve as a point of orientation for other centres and help improve the discrimination between pathological and normal results.…”
Section: Discussionsupporting
confidence: 61%
“…No identified study specifically addressed the worksheet question, however. Multiple analytical and pre‐analytical factors have been shown to influence TEG results in companion animals (LOE 2–3, Good‐Fair), and in people (LOE 6, Good‐Fair), suggesting that due consideration to such variables should be given when establishing reference intervals. Guidelines from nontarget species (LOE 6, Good) suggest that 40 individuals are required for accurate calculation of reference intervals based on the 2.5–97.5th percentiles, although use of robust methods may enable reference intervals to be calculated from 20 individuals .…”
Section: Assay Guidelines and Evidence Summariesmentioning
confidence: 99%
“…Multiple studies (LOE 2–6, Good‐Fair) have reported methods for calculation of TEG/ROTEM reference intervals. No identified study specifically addressed the worksheet question; however, multiple analytical and preanalytical factors have been shown to influence TEG results in companion animals and in people, suggesting that due consideration to such variables should be given when establishing reference intervals.…”
Section: Evidence Summarymentioning
confidence: 99%